Variasi Struktur Teks Resensi Dan Implementasinya Sebagai Bahan Ajar Di Sekolah Menengah Atas - Permatasari, Annisa; , Drs. Agus Budi Wahyudi, M.Hum (2016)
The purposes of this study are (1) to describe the elements of text structure builder reviewer. (2) to determine the structural variation of the text reviewer in magazines and newspaper. (3) to describe the structure of the text reviewer in writing class for teaching materials in senior high school. This research uses descriptive qualitative method. the data in this research uses descriptive qualiltative method. The data in this research are 30 texts reviewer who published in technique see, and technical notes. The validity of the data in this study is tested by triangulation. The method of analyzing the data used is unified referential with the basic technique aggregated as a differentation referent power. The results of this analysis are the variation of the structure reviewer who published in magazines and newspapers are 14 variations of the structure of the text. The 14 variations in the structure of the text reviews include (1) pattern 1 there is one datum, (2) pattern 2 there is one datum, (3) pattern 3 there are four pieces of data, (4) pattern 4 there is one datum, (5) pattern 5 there are two data, (6) pattern 6 there is one datum, (7) pattern 7 there is one datum, (8) pattern 8 there is one datum, (9) pattern 9 there are two data, (10) pattern 10 there are five data, (11) pattern 11 there is one datum, (12) pattern 12 there is one datum, (13) pattern 13 there is one datum, (14) patterns 14 there are two data. The results of this study can be implemented as teaching materials in a writing text reviewer on senior high school in class XII semester 1 on and experience in the from of reviews and short stories. On the basic competence (8.1) write a review of the book collection based on elements of the reviewer. Keywords: Elements Builders of Text and Text Structure Variation Reviewer.